Multisensory Human-Food Interaction - Kasun Karunanayaka (Frontiers Research Topics, 2018)
Our food experiences can be significantly influenced by both intrinsic and extrinsic multisensory information. Therefore, it is crucial to understand and apply the principles that govern the systematic connections that exist between the senses in the context of Human-Food Interaction (HFI). In our Research Topic, namely Multisensory Human-Food Interaction (MHFI), several studies that consider such connections in the context of HFI are presented. We also have contributions that focus on multisensory technologies that can be used to share and reproduce specific HFIs. This eBook, which resulted from the Research Topic, presents some of the most recent developments in the field of MHFI. In particular, it consists of two main sections and corresponding articles. The eBook begins with the Editorial, which provides an overview of MHFI. Then, it includes six articles that relate to principles in MHFI and three on technologies in MHFI. We hope that the different contributions featured here will support future developments in MHFI research.